Proteinuria as a Nascent Predictor of Frailty Among People With Metabolic Syndrome: A Retrospective Observational Study - Chang, Pi-Kai; Chao, Yuan-Ping; Wu, Li-Wei (Frontiers in Public Health, 2022)
Frailty is a commonly occurring geriatric condition that increases the risk of adverse health outcomes. The factors and predictors behind frailty are not yet well understood. A better understanding of these factors can enable prevention of frailty in elderly patients. The objective of this study was to determine the association between proteinuria and frailty in US individuals with metabolic syndrome (MetS). Data from the National Health and Nutrition Examination Survey III (NHANES III, 1988-1994) conducted by the National Center for Health Statistics of the Centers for Disease Control and Prevention. This is a cross-sectional study, and proteinuria and frailty were measured only once at enrollment. The study included 2,272 participants with MetS aged 40–90 years from the NHANES III. The participants underwent assessments to evaluate frailty and frailty components (low body weight, weakness, exhaustion, low physical activity, and slow walking). Proteinuria was represented as albumin-to-creatinine ratio (ACR) (mg/g) and divided into tertiles: T1-normal range (ACR < 30 mg/g), T2-microalbuminuria (ACR 30–299 mg/g), and T3-macroalbuminuria (ACR ≥ 300 mg/g). We applied multiple logistic regression to determine the odds ratios (ORs) of frailty for T2 versus T1 and T3 versus T1 in both sexes. In the adjusted analysis for male participants, the ORs of frailty for T2 and T3 versus T1 were 3.106 (95% confidence interval [CI] = 1.078–8.948, P = 0.036) and 14.428 (95% CI = 4.231–49.193, P < 0.001), respectively. For female participants, the ORs of frailty for T2 and T3 versus T1 were 1.811 (95% CI = 1.071–3.063, P = 0.027) and 2.926 (95% CI = 1.202–7.124, P =0.018), respectively. The positive association between T2 and T3 versus T1, and frailty were statistically significant. The trends of higher likelihood of every frailty component were also statistically significant across increasing tertiles of proteinuria after multiple levels of adjustment for covariates (P < 0.05). Increased proteinuria levels were positively associated with frailty and each frailty component. Proteinuria might be a useful maker for frailty in individuals with MetS.